Chemical Composition of Straw as an Alternative Material to Wood Raw Material in Fibre Isolation - Željka Barbarić-Mikočević (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Wood is still the most widely used raw material for pulp and paper production in the world. However, due to the necessity to supply the paper industry with raw materials used in the extraction of cellulose fibres and the overexploitation of forests, new sources of primary pulp fibres had to be identified. The aim of this research is to highlight the important features of cereal crop residues and their utilization in the paper industry. As the chemical composition of plant materials is one of the most important indicators of how such materials can be used in paper production, the analysis of the chemical composition of straw with the highest grain production was performed. The straw, as a harvesting residue, is a fibre resource available from the annually renewable crops, produced abundantly in numerous regions all over the world. For the purpose of the research, wheat, triticale and barley straw were selected for the analysis. The analysis of carbohydrate, lignin and extraneous material (organic extractives and inorganic minerals) was performed in order to obtain the straw chemical composition. Based on the results of the chemical composition of all analysed straw, it was confi rmed that straw, as an agricultural by-product, is rich in cellulosic fibres and, therefore, a valuable raw material for the paper industry. Out of all analysed straw, based on the results of their chemical composition, triticale straw is considered potentially the best source of alternative cellulose fibres.